2020
DOI: 10.1080/00981389.2020.1847747
|View full text |Cite
|
Sign up to set email alerts
|

Social care for older people – a blind spot in the Norwegian care system

Abstract: A growing number of older people in Norway receive care services at home. Public policy aims at promoting social safety, preventing social problems and providing recipients of care with the means to live an active and meaningful everyday life together with others. However, health-related services have long been prioritized at the expense of other care services. Our aims are to investigate how professional caregivers in Norwegian home care for older people relate their professional mandate to social care to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Home health nursing includes services that range from practical help and psychosocial support to more advanced medical treatment, such as the administration of medication and wound care. Social home care is regulated rather loosely and regarded as an embedded part of health home care (Schönfelder et al, 2020). Most patients are elderly individuals with varying, often chronic, illnesses, disabilities or frailty.…”
Section: Home Health Care and The Purchaserprovider-split Model In A ...mentioning
confidence: 99%
“…Home health nursing includes services that range from practical help and psychosocial support to more advanced medical treatment, such as the administration of medication and wound care. Social home care is regulated rather loosely and regarded as an embedded part of health home care (Schönfelder et al, 2020). Most patients are elderly individuals with varying, often chronic, illnesses, disabilities or frailty.…”
Section: Home Health Care and The Purchaserprovider-split Model In A ...mentioning
confidence: 99%
“…Schonfelder et al conducted interviews with 16 professional caregivers to investigate how professional caregivers in home care for the elderly in Norway relate their professional tasks to the social care [8]. Suwa et al investigated and analyzed the views of Japan, Ireland, and Finland on the participation of robots in home care for the elderly by means of questionnaires [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study of Norwegian nursing homes found that residents tend to experience sadness and loneliness as a result of a lack of meaningful communication with other residents and the nursing staff ( 10 ). Although long-term care facilities provide their residents with a wide range of services to assist with their medical and non-medical needs, they frequently fall short on providing sufficient social and emotional care ( 9 , 11 ). Most institutionalized older adults are therefore dependent on family members and friends to uphold their social well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors at the organizational level can also contribute to the risk of social isolation, including staff shortage and high turnover ( 6 , 25 ). Due to constrains in time and resources, healthcare workers often find themselves compelled to prioritize residents’ essential care needs, leaving limited room for addressing their social and emotional needs ( 6 , 11 ). Moreover, the high staff turnover rate often observed in long-term care facilities can be disruptive to residents’ sense of continuity and familiarity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation